Biotic relationships of Illex coindetii and Todaropsis eblanae (Cephalopoda, Ommastrephidae) in the Northeast Atlantic: Evidence from parasites - Pascual, Santiago; González, Ángel F.; Arias, C.; Guerra, Ángel (Sarsia, 1996)
10 páginas, 4 figuras, 5 tablas Parasites were collected from 1,200 short-finnedsquid(Illex coindetii,Todaropsis eblanae) cutghtwbycatch in a multispecies trawling fishery in the northwest Spanish Atlantic waters in 1992-1993. Parasites found included sixspecies ofhelrninths, three tehaphyllidean cestodes (Pftyl/obothriumsp.,Pelichnibothrium speciosum, Dinobothrium sp.), two trypanorhlmchidean cestodes (Nybelinia yanagutii, Nybelinia Iingualis),andone ascaridoid nematode(Anisakis simplexB). Two ofthesepar:asites(Plryllobothriumsp., A. simplexB), which could be recognised as component species, were used in analyses ofhost-parasite relationships. Levels ofinfection varied significantly with host size or stage ofmaturation for both squid species. Regional variation in infection level seems athibutable to geographical vari¿tion in availability of prey, discreteness and movements ofhost populations and to size or age-related changes in the prey selection oftheir host. Parasite evidences suggest that both ommastrephid squids are sympatric species sharing simila¡ econiches, and serve as diet for large top predators (selachians and marine mammals) ofNortheast Atlantic. Parasites may also be useful as an indirect indicatór ofthe migratory habits ofthe squid. Peer reviewed